2019
DOI: 10.4103/ijpsym.ijpsym_154_18
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis and Intervention for Autism Spectrum Disorder: Need for Pediatrician-Child Psychiatrist Liaison

Abstract: Background: Early interventions in children with autism spectrum disorder (ASD) reduce progressive symptom development. Delay in diagnosis and initiation of ASD-specific interventions is observed across settings. This study aimed to assess the trends in time to diagnosis and treatment initiation in a tertiary care pediatric setting. Methodology: Families of children with ASD ( n = 50) were assessed, and details regarding age at first symptom r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…We included 56 studies that reported the mean and/or median age at ASD diagnosis, of which 46 reported an overall ASD mean age at diagnosis between 30.9 and 574.4 months (Becerra-Culqui et al, 2018; Begeer et al, 2013; Bello-Mojeed et al, 2017; Bent et al, 2015; Berg et al, 2018; Bravo Oro et al, 2012; Brett et al, 2016; Carias & Wevrick, 2019; Cawthorpe, 2018; Crane et al, 2016; Daniels et al, 2017; Darcy-Mahoney et al, 2016; Emerson et al, 2016; Garrido et al, 2018; Goodwin et al, 2017; Hagberg & Jick, 2017; Hall-Lande et al, 2018; Hausman-Kedem et al, 2018; Höfer et al, 2019; Hrdlicka et al, 2016; Jo et al, 2015; Kentrou et al, 2019; Kurasawa et al, 2018; Lagunju et al, 2014; Larsen, 2015; Lo et al, 2017; Magaña et al, 2013; Manohar et al, 2019; Martinez et al, 2018; Masri et al, 2013; May et al, 2017; Mazurek et al, 2014; Miodovnik et al, 2015; Mishaal et al, 2014; Mpaka et al, 2016; Ribeiro et al, 2017; Rutherford et al, 2016; Salomone et al, 2016; Sheldrick et al, 2017; Shrestha et al, 2019; Sicherman et al, 2017; Talero-Gutiérrez et al, 2012; Ververi et al, 2012; Wei et al, 2018; Zablotsky et al, 2018). Of the 56 studies, 24 reported an overall ASD median age at diagnosis (only or combined with mean age at diagnosis score) between 28 and 96 months (Baio et al, 2018; Becerra-Culqui et al, 2018; Bent et al, 2015;…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 56 studies that reported the mean and/or median age at ASD diagnosis, of which 46 reported an overall ASD mean age at diagnosis between 30.9 and 574.4 months (Becerra-Culqui et al, 2018; Begeer et al, 2013; Bello-Mojeed et al, 2017; Bent et al, 2015; Berg et al, 2018; Bravo Oro et al, 2012; Brett et al, 2016; Carias & Wevrick, 2019; Cawthorpe, 2018; Crane et al, 2016; Daniels et al, 2017; Darcy-Mahoney et al, 2016; Emerson et al, 2016; Garrido et al, 2018; Goodwin et al, 2017; Hagberg & Jick, 2017; Hall-Lande et al, 2018; Hausman-Kedem et al, 2018; Höfer et al, 2019; Hrdlicka et al, 2016; Jo et al, 2015; Kentrou et al, 2019; Kurasawa et al, 2018; Lagunju et al, 2014; Larsen, 2015; Lo et al, 2017; Magaña et al, 2013; Manohar et al, 2019; Martinez et al, 2018; Masri et al, 2013; May et al, 2017; Mazurek et al, 2014; Miodovnik et al, 2015; Mishaal et al, 2014; Mpaka et al, 2016; Ribeiro et al, 2017; Rutherford et al, 2016; Salomone et al, 2016; Sheldrick et al, 2017; Shrestha et al, 2019; Sicherman et al, 2017; Talero-Gutiérrez et al, 2012; Ververi et al, 2012; Wei et al, 2018; Zablotsky et al, 2018). Of the 56 studies, 24 reported an overall ASD median age at diagnosis (only or combined with mean age at diagnosis score) between 28 and 96 months (Baio et al, 2018; Becerra-Culqui et al, 2018; Bent et al, 2015;…”
Section: Resultsmentioning
confidence: 99%
“…The wider mean and median ranges might be explained by the ages of the study populations. Studies that reported a lower or partly lower mean or median age in comparison to those included in the Daniels and Mandell (2014) review all included populations with children aged ⩽10 years (Christensen, Baio, et al, 2016; Christensen et al, 2019; Garrido et al, 2018; Manohar et al, 2019; Mishaal et al, 2014) or had a majority of the children aged ⩽10 years (Jo et al, 2015). Thus, the age at ASD diagnosis among these younger populations is logically lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Academy of Pediatrics recommended to screening at 18 and 24 months of age for ASD (15). Early diagnosis is critical because early interventions can provide the best opportunity to promote healthy development and provide lifelong benefits (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Manohar et al [2] has looked into the temporal trends from the earliest symptom recognition through pediatric consultation and time of diagnosis to time of the first specific intervention. The figures brought out are somewhat comforting than the ones published in previous studies.…”
mentioning
confidence: 99%